Vol. 30 Del. Laws 55, 55-56 (1919) - (:unkn) unknown (General Publisher, 1919)
Prohibited the sale to any minor or intoxicated person, any revolver, pistol, revolver cartridge, pistol cartridge, stiletto, steel knuckles, brass knuckles, or other deadly weapons made for the defense of one's person.
--
Keywords: TRANSFER - DANGEROUS PERSONS